Economic Feasibility of Kemojo Cake Products Using Stevia Extract (Stevia rebaudiana B.) - Dita Fitriani; Kurnia Harlina Dewi; Daimon Syukri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study aims to determine the feasibility of kemojo cake products using stevia as a sweetener produced on an industrial scale. The research method used a descriptive method with mathematical analysis. The research begins with making assumptions and analysing parameters, components and cost structure, investment funding requirements and working capital. These parameters calculate production, revenue, and cash flow projections. Determination of the economic feasibility of kemojo cake products with Net Present Value (NPV), Incremental Rate of Return (IRR), Net B/C and Pay Back Period (PBP). The assumption of a year's production of kemojo cakes is 31,680 boxes for at IDR 35,000.00/box. The proportion of capital comes from 60% own capital and 40% credit. The average operational costs per year are IDR 675,083,359.00, variable costs IDR 549,813,919.00 and fixed costs IDR 125,269,440.00. The average income per year is IDR 1,108,800,000.00 while expenses are IDR 770,378,416.00. The profit earned was IDR 287,658,346. Profit on sales of 20.40% with 15% tax per year. This business BEP occurs in sales of an average value of Rp 338,421,584 or 25.94% of production capacity per year. The results showed that the NPV was Rp 279,583,647, the IRR was 79%, and the Net B/C was 2.22 times. Based on existing criteria or assumptions, this business is feasible to carry out with PBP for two years, or the capital invested in this business can be returned before the project ends (3 years).